2020
DOI: 10.12800/ccd.v15i44.1468
|View full text |Cite
|
Sign up to set email alerts
|

Adherencia a la dieta mediterránea en escolares de Educación Primaria partícipes en actividad física: una revisión sistemática

Abstract: En la actualidad, existe una clara tendencia del abandono del estilo de vida mediterráneo, en especial en niños y adolescentes. La dieta mediterránea se postula como una de las formas de alimentación más saludables que existen. Conocer la adherencia a la dieta mediterránea en escolares resulta de interés, ya que podrían desplegarse acciones para promover una alimentación saludable, especialmente desde la asignatura de Educación Física. Esta es una revisión sistemática de estudios transversales que determinaron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
7
1
1
Order By: Relevance
“…This fact could be explained by the low proportion of children who met the PA recommendations in our study (about one in three participants) and the low number of participants with high MD (one in four children). This low proportion of children with high adherence to the MD is in line with the tendency towards the abandonment of the MD, especially in youths [24]. Nevertheless, we found higher mean values of KIDMED score were shown for those who meeting the PA recommendations, especially in girls.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This fact could be explained by the low proportion of children who met the PA recommendations in our study (about one in three participants) and the low number of participants with high MD (one in four children). This low proportion of children with high adherence to the MD is in line with the tendency towards the abandonment of the MD, especially in youths [24]. Nevertheless, we found higher mean values of KIDMED score were shown for those who meeting the PA recommendations, especially in girls.…”
Section: Discussionsupporting
confidence: 82%
“…In terms of eating habits, Mediterranean Diet (MD) is classified among the healthiest eating patterns in the world [21] given its specific properties, the type of food consumed, as well as an active lifestyle [22]. However, a worrying tendency towards the abandonment of the MD in children and adolescents has been indicated [23,24]. On this concern, the most of the studies performed show a positive relationship between MD adherence and PA [23].…”
Section: Introductionmentioning
confidence: 99%
“…Cuervo et al (2018) encontraron resultados similares, defendiendo que las personas que practican más deporte manifiestan un mayor interés por la alimentación. Camargo et al (2020) también apuntan a esta relación positiva entre la práctica de la actividad física y la adquisición de hábitos saludables haciendo hincapié en el papel de la Escuela y de la Educación Física a la hora de adherirse a una dieta saludable.…”
Section: Discussionunclassified
“…Specifically, among young people, greater adherence to the MedDiet has been associated with greater anti-inflammatory potential [ 19 ]. Unfortunately, even though it is a healthy dietary pattern supported by evidence, a systematic review has pointed out the clear trend of decreasing adherence to the MedDiet in Mediterranean countries, especially among children [ 20 , 21 ]. For instance, Cabrera et al [ 20 ] reported an overall rate of only 10% with high adherence to the MedDiet among a young population.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding MedDiet, only one previous cross-sectional study (in adolescents) has found that meeting all three 24-h movement guidelines has been related to greater adherence to the MedDiet compared to those who did not meet these guidelines [ 30 ]. It is possible that the low prevalence of 24-h movement guidelines reported worldwide [ 10 ] and in Spain [ 28 ] may be another factor to be taken into account in the low adherence to the MedDiet currently described [ 20 , 21 ]. Although the need for interventions focusing on improving adherence to the 24-h movement guidelines [ 10 ] and MedDiet [ 25 ] has been previously suggested, the literature on this matter is limited.…”
Section: Introductionmentioning
confidence: 99%